Defining and Diagnosing Obesity in India: A Call for Advocacy and Action - Sanjay Kalra; Nitin Kapoor; Madhur Verma; Shehla Shaikh; Sambit Das; Jubbin Jacob; Rakesh Sahay (Journal of Obesity)
The prevalence of overweight and obesity has more than doubled since 1980, and it is predicted that around two-thirds of the global burden of the disease will be attributed to chronic non-communicable diseases. Developing countries are experiencing a more dramatic rise in the prevalence of obesity in recent years. As per National Family Health Survey-5 (NFHS-5), one in every four Indians is now having obesity. It has been reported that being overweight and obese is a significant problem among different socioeconomic spectrums of men and women in India, especially among the elderly, people residing in urban regions, and diverse socioeconomic strata. There is an urgent need to identify obesity as a chronic disease requiring immediate attention, mandating timely screening, timely treatment, and economical ways of achieving and managing weight loss across the country. In this review, the authors have discussed various aspects of overweight and obesity and critically appraised the current status of obesity in India, its public health implications, the significance of screening, the role of BMI and other parameters in diagnosing obesity, and the need for treatment and cost-effective prescriptions.